2019
DOI: 10.3389/fbioe.2019.00214
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of the Pharmacological Profiles of Degradation Products of Chitosan

Abstract: Chitosan is a natural polymer revealing an increased potential to be used in different biomedical applications, including drug delivery systems, and tissue engineering. It implies the evaluation of the organism response to the biomaterial implantation. Low-molecular degradation products, the chito-oligomers, are resulting mainly from the influence of enzymes, which are found in the organism fluids. Within this study, we have performed the computational assessment of pharmacological profiles and toxicological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 101 publications
2
24
0
Order By: Relevance
“…Quite similar results with those emphasized in this study were obtained when assessing the pharmacological profiles of the short oligomers resulting from the degradation of other biopolymers that are used for medical applications: oligomers (up to 40 monomeric units) of lactic acid (OLAs) (Dascalu et al, 2020) and low molecular weight chito-oligosaccharides (Roman et al, 2019). OLAs were also predicted as being able to inhibit the organic anion transporting peptides OATP1B1 and/or OATP1B3.…”
Section: O4hbv O4hvb O4hbvb O4hbvv 04hvbv O4hvbbsupporting
confidence: 84%
See 2 more Smart Citations
“…Quite similar results with those emphasized in this study were obtained when assessing the pharmacological profiles of the short oligomers resulting from the degradation of other biopolymers that are used for medical applications: oligomers (up to 40 monomeric units) of lactic acid (OLAs) (Dascalu et al, 2020) and low molecular weight chito-oligosaccharides (Roman et al, 2019). OLAs were also predicted as being able to inhibit the organic anion transporting peptides OATP1B1 and/or OATP1B3.…”
Section: O4hbv O4hvb O4hbvb O4hbvv 04hvbv O4hvbbsupporting
confidence: 84%
“…The co-oligomers containing the sequences 3-hydroxybutyrate-3-hydroxyvalerate or 4-hydroxybutyrate-4hydroxyvalerate revealed to have the highest probabilities to bind to plasma proteins. Low probabilities to bind to plasma proteins have been also predicted for low molecular weight chitosan based oligomers (Roman et al, 2019) and low molecular weight oligomers of lactic acid (Dascalu et al, 2020). This outcome is also in good agreement with the information that the binding of 4HB to plasma proteins is negligible and its distribution on the human organism depends on its distribution in the total body water (Busardò and Jones, 2015).…”
Section: O4hbv O4hvb O4hbvb O4hbvv 04hvbv O4hvbbsupporting
confidence: 79%
See 1 more Smart Citation
“…Carcinogenicity is one of the cell-killing property of the chemical compound. To know the carcinogenicity nature of the compound CarcinoPred-EL was used (Mady et al, 2018;Roman et al, 2019).…”
Section: Carcinogenicity Nature Of the Compoundsmentioning
confidence: 99%
“…Pharmaceutical actions of COs proved to be strongly dependent on their physicochemical properties [18]. A computational study performed by our group [19] showed that COs reveal promising pharmacological profiles and limited toxicological effects on humans, regardless of MW, DD, and DAP. According to this study, the possible toxicological effects of COs in the human organism consist in the inhibition of the organic anion transporting peptides OATP1B1 and/or OATP1B3, a small probability of affecting the androgen receptor, a low potential of cardiotoxicity, and the possibility of COs characterized by high DD to produce phospholipidosis [19].…”
Section: Introductionmentioning
confidence: 99%